Smart Power Management and Delay Reduction for Target Tracking in Wireless Sensor Networks. (11th March 2014) - Feng, Juan; Lian, Baowang; Zhao, Hongwei
Abstract : Energy efficiency and data transmission delay are critical issues for mobile target tracking wireless sensor networks, in which abundant sensor nodes are deployed to collect the target information from the sensing field. At present, many existing works have been concentrated on extending network lifetime, while less emphasis was placed on both transmission delay reduction and the adaptive sleep of sensor nodes considering the application constraints. In this paper, we propose a smart power management and delay reduction approach for target tracking based on a grid network structure, where sensor nodes adjust their sleep intervals according to the distance between the node and the moving target. Sensor nodes can distributedly decide their sleeping time using the information from their neighbors. Furthermore, we propose a real-time chain to relay the sensed data for transmission delay reduction. The proposed approach allows sensor nodes that are far away from the target to sleep more and make the target information forward to the sink in time. Experimental results verify that, in contrast to adaptive coordinate and local power management protocols, the proposed approach achieves a significant energy saving while maintaining a short transmission delay.